2017
DOI: 10.1016/j.cell.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Nuclear Lamina Interactions Regulate Cardiac Stem Cell Lineage Restriction

Abstract: Summary Progenitor cells differentiate into specialized cell types through coordinated expression of lineage-specific genes and modification of complex chromatin configurations. We demonstrate that a histone deacetylase (Hdac3) organizes heterochromatin at the nuclear lamina during cardiac progenitor lineage restriction. Specification of cardiomyocytes is associated with reorganization of peripheral heterochromatin and, independent of deacetylase activity, Hdac3 tethers peripheral heterochromatin containing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
220
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(261 citation statements)
references
References 54 publications
22
220
1
Order By: Relevance
“…Histone H3 lysine 9 dimethylation (H3K9me2) is enriched at the nuclear periphery and overlaps with LADs genome-wide (Kind et al, 2013; Peric-Hupkes et al, 2010; Poleshko et al, 2017; Wen et al, 2009). Disruption of the methyltransferases that deposit H3K9me2 by knockdown or inhibition has been shown to cause genes in LADs to move away from the nuclear periphery (Bian et al, 2013; Harr et al, 2015; Kind et al, 2013; Towbin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Histone H3 lysine 9 dimethylation (H3K9me2) is enriched at the nuclear periphery and overlaps with LADs genome-wide (Kind et al, 2013; Peric-Hupkes et al, 2010; Poleshko et al, 2017; Wen et al, 2009). Disruption of the methyltransferases that deposit H3K9me2 by knockdown or inhibition has been shown to cause genes in LADs to move away from the nuclear periphery (Bian et al, 2013; Harr et al, 2015; Kind et al, 2013; Towbin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…usRC has a similar organization and our functional dissection of this LAD border indicates that the CBEs and promoter elements cooperate to mediate LAD border activity. LADs have been shown to be enriched for H3K9me2 along their entire length, and this modification is thought to be essential for anchoring to the NL (Harr et al, 2015; Kind et al, 2013; Peric-Hupkes et al, 2010; Poleshko et al, 2017; Towbin et al, 2012; Wen et al, 2009). Our analysis of wild-type VL3-3M2 cells confirmed the correlation between DamID and H3K9me2 signals, both genome-wide and at the Tcrb locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] The complexity includes not only the hierarchical structures throughout all length scales, but also their highly dynamic adaptiont ot he environments.T he representative example is the stem cells, which can develop into differentt issues or organs depending on the environments. [9][10][11][12] It is highly important to develop artificial systems that can develop into different structures from the same startingm aterials upon the change of environments to help to understand such mystery phenomenona nd construct artificial intelligent systems. It has to be mentioned that the highly adaptive systemsh ere have inherentd ifferences from the ubiquitous systems in which different conditions lead to different products.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear lamina consisting of lamins and nuclear lamin‐associated membrane proteins is a fibrillar network structure that exists in the nucleus of most eukaryotic cells . Such a fibrillar network structure of nuclear lamina connects the inner nuclear membrane inside a nucleus, and the endoplasmic reticulum in cytoplasm not only providing the mechanical support of nucleus , but also involving several cellular events [e.g., chromatin organization , cell cycle regulation , cell differentiation , DNA replication ]. Reports in literature have demonstrated that the variations of mechanical properties of nuclei are associated with physiological and pathological status of cells including tumor development , stem cell differentiation , and blood cell relevant diseases .…”
mentioning
confidence: 99%